Bowman's Gland in Nasal Tissues: As A Possible - Hastari Wuryastuti; R. Wasito (Indonesian Association of Food Technologists, 1998)
We have investigated the Bowman's gland of the nasal cavity after in vivo study in the Sprague-Dawley rats to asses its biomarker potential in vitamin A nutritional study. Fourty-eight male weanling SpragueDawley rats at 3-4 weeks of age were allotted to four groups of 12 each and were fed diets either vitamin A-deficient or supplemented with 30.000 IU vitamin A/kg for 150 days. Rats in their respective groups were also given fume of vehicle for 150 days. Fumigation was done 2x/day for 1 hour each. Rats given vitamin A-deficient diet and fume of vehicle had the most extensive inhibition of glycoprotein synthesis in cells of Bowman's gland in the olfactory region of the nasal cavities as determined by severe loss of Alcian blue-periodic acid-Schiff staining material. Histochemical lesions were not seen in nasal cavity of vitamin A-supplemented rats